From Languishing Dyslexia to Thriving Dyslexia: Developing a New Conceptual Approach to Working with People with Dyslexia - Kannangara, Chathurika S. (Frontiers in Psychology, 2015)
This is an account of personal narratives shared by several people with dyslexia. Most of these are presented in their original quotation format to provide personal accounts of the lives of people with dyslexia. In this paper the author shares her conversations with her participants. This paper provides an original conceptual model, which is currently been tested empirically. Dyslexia affects the learning process in areas as such reading, and spelling. Conversely abilities or strengths can be seen in other areas, such as developing coping strategies to manage and overcome challenges. This research aims to adapt positive psychology techniques to support individuals with dyslexia. To develop positive psychology interventions, individuals will be helped to discover their five signature strengths. The VIA (Values in Action) Strengths Survey has been hosted in a website which has been developed in the form of a dyslexia user friendly format, such as providing the ability for respondents to change fonts and font sizes, colours and a text to speech option. This paper introduces the theoretical model of ' How to move from Languishing Dyslexia to Thriving Dyslexia'.